2011
DOI: 10.1007/s11999-010-1453-y
|View full text |Cite
|
Sign up to set email alerts
|

The Salto Total Ankle Arthroplasty: Survivorship and Analysis of Failures at 7 to 11 years

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(180 citation statements)
references
References 43 publications
7
169
1
3
Order By: Relevance
“…Failure causes include aseptic loosening, subsidence, cysts formation, peri-prosthetic and polyethylene fracture (Conti and Wong, 2001;Besse et al, 2009;Bonnin et al, 2011;Labek et al, 2011;Brunner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Failure causes include aseptic loosening, subsidence, cysts formation, peri-prosthetic and polyethylene fracture (Conti and Wong, 2001;Besse et al, 2009;Bonnin et al, 2011;Labek et al, 2011;Brunner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rippstein et al reported 97.7% after 4 years in TAR using the Mobility prosthesis (13). Bonnin et al noted 65.2% after 10 years in TAR using the Salto Prosthesis (14). Furthermore, Courville et al concluded in a costeffective analysis of a hypothetical 60 year old cohort that TAR remained cost effective alternative to ankle arthrodesis despite newer costly implants and longer follow-up (15).…”
Section: Ankle Arthroplastymentioning
confidence: 99%
“…However, fusion has several limitations including decreased function, adjacent joint degeneration and altered gait mechanics. [58][59][60] Total ankle arthroplasty has seen a resurgence of interest due to improved technology and survivorship [61][62][63] Nevertheless, there is limited data on long-term outcomes, with a recent comparison of arthrodesis to replacement demonstrating high rates of complications and reoperation. 64 Furthermore, implants were designed for use in older, lower-demand patients, and younger, more active patients may experience inferior function and shorter implant survival.…”
Section: End-stage Arthritis Of the Anklementioning
confidence: 99%